A ruined temple to the north of the Mahanaleshwar temple complex - Temples of India Project Team (Jio Institute, 2024)
Similar to the western boundary of the Mahanaleshvar temple complex, the northern side also has two temples which stand close to the main temple. Seen here is a ruinous shrine bereft of any ornamentation. Its superstructure has not survived. It consists of a row of small cells which is fronted by a colonnade. The pillars of the colonnade have plain shafts.